Development of open-cell polyurethane-based bone surrogates for biomechanical testing of pedicle screws. (September 2019) - Hollensteiner, Marianne; Esterer, Benjamin; Fürst, David; Schrempf, Andreas; Augat, Peter
Abstract: Artificial bones made of polyurethane are frequently used as an alternative to human bone for biomechanical testing. However, the biomechanical characteristics of these materials are often not validated against those of human bones. Thus, synthetic bone surrogates reflecting procedure-specific biomechanical properties of human bones are necessary for reliable implant design and testing. The aim of this study was to evaluate novel custom made open- and close-cell bone surrogates through morphometry assessment and pedicle screw pullout tests as an alternative to human bone for biomechanical testing. Bone surrogates created from polyurethane resin, mineral fillers and varying amounts of blowing agent were customized to various densities. Pedicle screws were manually inserted and pullout tests with a feed rate of 1 mm/min were conducted until failure. Load and displacement curves were recorded and analyzed in terms of maximum pullout forces. The resulting pullout forces of open- (1437 ± 665 N) and close-cell surrogates (951 ± 578 N) showed comparable results to human bone (1417 ± 812N) used as a reference. Furthermore, structural morphometric parameters were in accordance with human vertebral cancellous bone. In conclusion, the customized bone surrogates provide a new opportunity to design and test pedicle screws and further study the relationship between biomechanical properties and apparent density of artificial spongy bone.